2014
DOI: 10.1371/journal.pntd.0003298
|View full text |Cite
|
Sign up to set email alerts
|

Topography and Land Cover of Watersheds Predicts the Distribution of the Environmental Pathogen Mycobacterium ulcerans in Aquatic Insects

Abstract: BackgroundAn understanding of the factors driving the distribution of pathogens is useful in preventing disease. Often we achieve this understanding at a local microhabitat scale; however the larger scale processes are often neglected. This can result in misleading inferences about the distribution of the pathogen, inhibiting our ability to manage the disease. One such disease is Buruli ulcer, an emerging neglected tropical disease afflicting many thousands in Africa, caused by the environmental pathogen Mycob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…They can also infect humans outside aquatic environments because of their ability to fly many kilometers away from their source (61,152). In Cameroon, M. ulcerans DNA was detected in communities of aquatic macroinvertebrates and vertebrates (153,154).…”
Section: Detection Of M Ulcerans In Insects and Aquatic Animalsmentioning
confidence: 99%
“…They can also infect humans outside aquatic environments because of their ability to fly many kilometers away from their source (61,152). In Cameroon, M. ulcerans DNA was detected in communities of aquatic macroinvertebrates and vertebrates (153,154).…”
Section: Detection Of M Ulcerans In Insects and Aquatic Animalsmentioning
confidence: 99%
“…Buruli ulcer occurs mostly in low-lying swampy areas [ 9 , 10 ]. Epidemiological studies have shown that the aquatic environment is the main reservoir of M .…”
Section: Introductionmentioning
confidence: 99%
“…Deforestation is known to affect incidence of Buruli ulcer and may thus influence MU infection prevalence as well (Brou et al , Wagner et al ). Indeed land cover variables influence MU prevalence (Carolan et al ) and, among a wide spectrum of landscape variables, previous studies showed that deforestation explains the most variation in MU prevalence in French Guiana, South America (Morris ). Therefore, as a source of variation that may confound our analysis we considered the effects of deforestation on MU infection prevalence.…”
Section: Methodsmentioning
confidence: 99%